A limit theorem for partial weighted sums of regression residuals - Pažemys, Vytenis (Lietuvos matematikos rinkinys, 2004)
Let a linear regression be given. We consider the polygonal line process of weighted least squares residuals. We prove a limit theorem in Hoder spaces for this process. This extends the results of Jandhyala and MacNeill, Bischoff, Račkauskas.